Do indirect tests of English intonation measure students' ability in performing English nucleus placement? (Philologia, 2021)
This study focuses on nucleus placement in English intonation and attempts to investigate (1) the reliability and validity of indirect tests on nucleus placement, and (2) the credibility of English proﬁciency tests as a predictor of students’ ability in nucleus placement. Three tests were administered to 111 Japanese EFL university students: (a) an English proﬁciency test, (b) an indirect test on nucleus placement, and (c) a direct test (oral performance test) on nucleus placement.The results obtained are: [1] the internal reliability of the direct test was very high, but the internal reliability of the indirect test was very low, and [2] there were no signiﬁcant correlations among the three tests. These results indicate that indirect tests and English proﬁciency tests cannot predict the students’ performance of nucleus placement. This research also made us realize the responsibility of teachers to receive adequate phonetic training to learn to auditorily discriminate between their students’ correct and incorrect performances.
Keywords: direct test; indirect test; intonation; nucleus placement; reliability; validity; National Centre for University Entrance Examinations